Pengaruh Kualitas Pelayanan dan Green Meeting terhadap Kepuasan Peserta Event Conference di Bali - Santi Arianti Palupi; Firman Sinaga (Journal of Tourism Destination and Attraction, 2021)
Bali is in the first place for frequency of conference events when compared to Jakarta. Bali is a very strategic place in the implementation of both national and international conferences, but its competitiveness is still below that of countries in the ASEAN. The research aims to analyze the effect of service quality and green meeting on conference participant satisfaction. The research method is a quantitative method with SEM data analysis with the AMOS program, using a likert scale. Determination of respondents carried out by accidential sampling. The results showed that: 1) service quality had a significant effect on conference participant satisfaction, 2) green meeting had a significant effect on conference participant satisfaction. The conclusion of this study is that service quality and green meetings are very important in a conference event because they affect the satisfaction of conference participants in Bali